\(17x-\left(-16x-37\right)=2x+43\)
\(17x+16x+37=2x+43\)
\(17x+16x-2x=43-37\)
\(31x=6\)
\(x=\frac{6}{31}\)
17x-(-16x-37)=2x+43
17x + 16x + 37 = 2x + 43
33x - 2x = 43 - 37
31x = 6
x = 6 : 31
x = \(\frac{6}{31}\)
Vậy x = \(\frac{6}{31}\)
Hok tốt !
\(17x-\left(-16x-37\right)=2x+43\)
\(\Leftrightarrow17x+16x+37=2x+4\)
\(\Leftrightarrow17x+16x-2x=4-37\)
\(\Leftrightarrow31x=-33\)
\(\Leftrightarrow x=\frac{-33}{31}\)
Vậy...
#Hiên
17x-(-16x-37)=2x+43
17x+16x+37=2x+43
17x+16x-2x=43-37
31x=6
x=\(\frac{6}{31}\)
\(17x\left(-16x-37\right)=2x+43\)
\(\Leftrightarrow17x+16x+37=2x+43\)
\(\Leftrightarrow17x+16x-2x=43-37\)
\(\Leftrightarrow31x=6\)
\(\Leftrightarrow x=\frac{6}{31}\)
\(17x-\left(-16x-37\right)=2x+43\)
\(17x+16x+37=2x+43\)
\(17x+16x-2x=43-37\)
\(31x=6\)
\(x=\frac{6}{31}\)
Vậy \(x=\frac{6}{31}\)